Unknown staurotheke-enkolpion of Prohegoumenos Matthaios (1645) from the Bachkovo Monastery in a private collection in Greece - Trifonova Alexandra Ph. (Zograf)
The article presents an unpublished staurotheke-enkolpion (1645) from the Bachkovo Monastery, held today in a private collection in Greece. The donor’s inscription on the staurotheke reveals that it was commissioned by hieromonk Matthaios, the prohegoumenos of the Bachkovo Monastery of the Virgin Petritsiotissa.